Analisis Tingkat Pengetahuan Swamedikasi Obat Batuk pada Pasien ISPA di Apotek Siaga-24 Cikampek - Adha Riyanti; Rida Emelia (Jurnal Health Sains, 2021)
Self-medication is a human behavior that people usually do to get solutions related to health problems, for this reason self-medication must be supervised by pharmacists. Cough is one of the symptoms of ARI that can be treated with self-medication. The purpose of this study was to find out how the level of knowledge of ARI patients on cough medicine self-medication at Apotek standby-24 Cikampek. And to know the role of pharmacy technical personnel in providing information about cough medicine self-medication. This study uses a quantitative descriptive method using a cross sectional research design. Data was collected by means of a questionnaire on 55 respondents. The population in this study were ARI patient with cough symtoms aged 15 to 50 years.  The sampling technique used was purposive sampling method. This research was conducted in April - May 2021. The results of this study showed that 95.83% of respondents had a high level of knowledge of cough medicine self-medication and 4.17% showed a low level of self-medication knowledge. Then 87.50% of pharmacy staff provided complete information on self-medication of cough medicine and 12.50% of pharmacy staff were incomplete in providing information on self-medication of cough medicine. The majority of respondents understand what type of cough they suffer from and understand the selection of cough medicine so that self-medication of cough medicine can be achieved according to symptoms